Association of dietary total antioxidant capacity, alternative healthy eating index, and dietary inflammatory index with semen quality in men seeking infertility treatment - Dabagh, Mahtab; Jahangiri, Nargesbano; Taheri Madah, Ali; Rostami, Sahar; Amidi, Fardin; Khodarahmian, Mahshad; Tavoosian, Ali; Shabani Nashtaei, Maryam; Vatannejad, Akram (Frontiers in Nutrition, 2023)
Background: Since the association between dietary quality scores and semen quality remains unclear, we carried out a hospital-based cross-sectional study to investigate the association of Dietary Total Antioxidant Capacity (dTAC), Dietary Inflammatory Index (DII), and Alternative Healthy Eating Index (AHEI) scores with semen quality in men seeking infertility treatment.This study enrolled 210 men with unexplained or idiopathic infertility. Semen samples were collected and analyzed according to the WHO 2010 criteria. Dietary data was collected using a 168-item semi-quantitative food frequency questionnaire (FFQ) developed for Tehran Lipid and Glucose Study. Multivariable logistic regression models were used to estimate the relationship between dTAC, AHEI, and DII scores with abnormal semen in crude and adjusted models.Results: There were no significant differences across quartile categories of the dTAC, AHEI, and DII scores regarding semen parameters. There was a trend toward a significant direct association between DII and abnormal semen risk (P = 0.01). Infertile men in the highest quartile of DII had a 2.84 times higher risk of abnormal semen in the crude model (OR: 3.84; 95 % CI: 1.64 -8.95); such that remained after adjusting for several potential confounders. There was no significant association between dTAC or AHEI and the risk of abnormal semen in infertile men, either before or after adjusting for potential confounders. Total energy (P = 0.05), fat (P = 0.02), saturated fat (P = 0.02), mono-saturated fat (P = 0.009), Thiamine (Vitamin B1) (P = 0.02), Niacin (Vitamin B3) (P = 0.03), Calcium (P = 0.01), and Selenium (P = 0.01) were inversely associated with semen normality.The study suggests that certain dietary factors may affect semen quality, and the mechanisms underlying the observed associations are likely multifactorial, involving complex interactions between diet, oxidative stress, inflammation, and hormone levels. Further research is required to confirm the results, fully elucidate the mechanisms underlying the associations, and identify specific dietary interventions that may improve male fertility outcomes.